Burkholderia cenocepacia conditional growth mutant library created by random promoter replacement of essential genes. Issue 2 (7th February 2013) - Bloodworth, Ruhi A. M.; Gislason, April S.; Cardona, Silvia T.
Abstract: Identification of essential genes by construction of conditional knockouts with inducible promoters allows the identification of essential genes and creation of conditional growth (CG) mutants that are then available as genetic tools for further studies. We used large‐scale transposon delivery of the rhamnose‐inducible promoter, P rhaB followed by robotic screening of rhamnose‐dependent growth to construct a genomic library of 106 Burkholderia cenocepacia CG mutants. Transposon insertions were found where P rhaB was in the same orientation of widely conserved, well‐characterized essential genes as well as genes with no previous records of essentiality in other microorganisms. Using previously reported global gene‐expression analyses, we demonstrate that P rhaB can achieve the wide dynamic range of expression levels required for essential genes when the promoter is delivered randomly and mutants with rhamnose‐dependent growth are selected. We also show specific detection of the target of an antibiotic, novobiocin, by enhanced sensitivity of the corresponding CG mutant (P rhaB controlling gyrB expression) within the library. Modulation of gene expression to achieve 30–60% of wild‐type growth created conditions for specific hypersensitivity demonstrating the value of the CG mutant library for chemogenomic experiments. In summary, CG mutants can be obtained on a large scale by random delivery of a tightly regulated inducible promoter into the bacterial chromosome followed by a simple screening for the CG phenotype, without previous information on gene essentiality. Abstract : We used transposon delivery of an outward‐facing rhamnose‐inducible promoter followed by screening of rhamnose‐dependent growth to construct a genomic library of 107 Burkholderia cenocepacia conditional growth (CG) mutants. Expression from the rhamnose promoter achieved the wide dynamic range of expression levels required for essential genes. Gene regulation to obtain 30–60% of wild‐type growth created conditions for specific hypersensitivity demonstrating the value of the CG mutant library for chemogenomic experiments.